1997
DOI: 10.1021/la960944v
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxamate Complexes in Solution and at the Goethite−Water Interface:  A Cylindrical Internal Reflection Fourier Transform Infrared Spectroscopy Study

Abstract: The infrared spectra of aqueous solutions of acetohydroxamic acid (aHA), an analogue for important iron(III) chelating ligands in soils and groundwaters, and of suspensions of goethite with adsorbed aHA were measured using a cylindrical internal reflectance cell. Using molecular orbital theory and data from the literature on the infrared spectra of solid hydroxamates and metal−hydroxamate complexes, we identify the spectral changes occurring upon complexation with both aqueous Fe(III) and Fe atoms on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 54 publications
2
53
1
Order By: Relevance
“…Holmen et al (1997) have elucidated the structure of the acetohydroxamic acid (aHA) surface complex on goethite by FTIR-spectroscopy. aHA adsorbs on the goethite-water interface by a ligand exchange reaction as shown in Figure 6.…”
Section: Adsorption Of Monohydroxamate and Monocatecholate Ligandsmentioning
confidence: 99%
“…Holmen et al (1997) have elucidated the structure of the acetohydroxamic acid (aHA) surface complex on goethite by FTIR-spectroscopy. aHA adsorbs on the goethite-water interface by a ligand exchange reaction as shown in Figure 6.…”
Section: Adsorption Of Monohydroxamate and Monocatecholate Ligandsmentioning
confidence: 99%
“…Hydroxamate siderophore-promoted dissolution rates, compiled from a number of sources (Hersman et al 1995;Lloyd 1999;Cocozza et al 2002;Neubauer et al 2002;Yoshida et al 2002;Cheah et al 2003;Carrasco et al 2007;Wolff-Boenisch and Traina 2007;Carrasco et al 2008) and spanning a large range of pH (3-9), concentration (1.3 9 10 -5 -10 -3 M), and solid phases [a-FeOOH, a-Fe 2 O 3 , and a poorly crystalline Fe(III)-hydroxide] vary by less than a factor of 20 (R = 10 -11.5 -10 -12.8 mol m -2 s -1 ), strongly suggesting commonalities among the mechanisms of hydroxamate siderophore-promoted dissolution. Desferrioxamine B promoted-dissolution of goethite appears to be surface-controlled (Cheah et al 2003) and possibly mediated by the formation of dissolutionactive bidentate mononuclear surface structures (Holmen et al 1997;Cocozza et al 2002). Interestingly, a number of low-molecular mass organic acids (LMMOAs; e.g., oxalate, citrate, malonate, succinate, and fumarate) have been shown to augment siderophore-promoted dissolution rates (Cheah et al 2003;Reichard et al 2007;Wolff-Boenisch and Traina 2007).…”
Section: Siderophore-promoted Dissolution Of Mn and Fe Mineralsmentioning
confidence: 99%
“…Liermann et al (2000) observed an approximately square-root dependence on DFO-B concentration for the Fe release rate from hornblende, leading them to conclude that DFO-B adsorption is necessary to mineral dissolution. Casey (1996, 1998) and Holmén et al (1997) have added mechanistic details to this picture in their careful investigations of the dissolution of goethite promoted by acetohydroxamic acid [CH 3 COHNOH,aHA], a simple monohydroxamate ligand. They concluded that the aHA hydroxamate group coordinates to a surface Fe(III) center on the mineral in much the same way as in aqueous solution (i.e., bidentate ligation), but does so with the greater impact of vicinal atoms in the mineral, as compared with solvating water molecules in aqueous solution, on the distribution of electron density within the surface complex.…”
Section: Introductionmentioning
confidence: 99%